Calle-Escenario : suma de acciones en el Alto Fucha (2019)
Through the application of addition of actions' system in the pilot street, Street 23 B East, in Alto Fucha, is reactivated the stretch of street considered. The conjunction of the different mechanisms used for the activation of the street derives in the appearance of a true urban suture process: the chosen street is perceived as a multiplicity of moments, a linearity constituted by the union of several points, a path endowed with places of permanence. In this way, the different parts of the system make sense. Initially, actions such as the creation of physical supports appear in pre-existing spaces, such as the San Jerónimo del Yuste forest and the Fucha river, generating the tension necessary to configure true attractors on both extremities. Likewise, there is the introduction of supports to public pocket spaces, the latters understood as activity centers in the area. Additionally, there are measures designed to rethink the relationship between public and private...